2014
DOI: 10.1371/journal.pone.0100392
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Safety and Efficacy Evaluation of a Recombinant Bovine Respiratory Syncytial Virus (BRSV) with Deletion of the SH Gene and Subunit Vaccines Based On Recombinant Human RSV Proteins: N-nanorings, P and M2-1, in Calves with Maternal Antibodies

Abstract: The development of safe and effective vaccines against both bovine and human respiratory syncytial viruses (BRSV, HRSV) to be used in the presence of RSV-specific maternally-derived antibodies (MDA) remains a high priority in human and veterinary medicine. Herein, we present safety and efficacy results from a virulent BRSV challenge of calves with MDA, which were immunized with one of three vaccine candidates that allow serological differentiation of infected from vaccinated animals (DIVA): an SH gene-deleted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 64 publications
3
44
0
Order By: Relevance
“…In the current study, we demonstrated that RSV ⌬SH protected against viral challenge in the mouse model. A recent study has demonstrated that a bRSV ⌬SH vaccine is highly protective in infant calves, even in the presence of maternal antibody (29), and a live attenuated RSV ⌬SH vaccine with additional point mutations (Medi-559) has been shown to be safe and immunogenic in clinical trials in children (30). Data from chimpanzee studies (31), which showed moderate attenuation, suggest SH alone would be insufficient for a safe live vaccine, though it has been shown to be highly effective in cattle (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we demonstrated that RSV ⌬SH protected against viral challenge in the mouse model. A recent study has demonstrated that a bRSV ⌬SH vaccine is highly protective in infant calves, even in the presence of maternal antibody (29), and a live attenuated RSV ⌬SH vaccine with additional point mutations (Medi-559) has been shown to be safe and immunogenic in clinical trials in children (30). Data from chimpanzee studies (31), which showed moderate attenuation, suggest SH alone would be insufficient for a safe live vaccine, though it has been shown to be highly effective in cattle (29).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that a bRSV ⌬SH vaccine is highly protective in infant calves, even in the presence of maternal antibody (29), and a live attenuated RSV ⌬SH vaccine with additional point mutations (Medi-559) has been shown to be safe and immunogenic in clinical trials in children (30). Data from chimpanzee studies (31), which showed moderate attenuation, suggest SH alone would be insufficient for a safe live vaccine, though it has been shown to be highly effective in cattle (29). While addition of ⌬SH to other temperature-sensitive vaccines had a marginal effect (32,33) on attenuation, we speculate that SH has an immunomodulatory function and that its deletion as part of a live attenuated RSV vaccine design would be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon needs to be taken into account since most of the preclinical studies to test/validate prototype vaccines for maternal immunization have used na€ ıve dams for vaccination. 9,30,31 In our study, the vaccine-induced protection of the litter was evidenced only later (4 weeks after birth), when waning of maternal immunity is more evident, in contrast to testing it on or close to the day of delivery, when most of the animals are fully protected independent of the vaccination status. Overall, this data strongly supports the idea that we must use a different set of conditions for testing prototype RSV vaccines in order to find a successful vaccine for vaccination during pregnancy.…”
Section: Inadequacy Of Current and Past Pre-clinical Rsv Vaccine Modelsmentioning
confidence: 45%
“…In a previous attempt to design chimeric N-nanorings fused to bovine FsII, we failed to generate anti-F antibodies in calves, strongly suggesting that bovine FsII was not correctly exposed. 25 In the present study, we fused an extended human FsII either at the N-terminus (Nter) or on the top of the β-hairpin located between G106 and K107 residues (G106) of N. Indeed, the two FsII-fused N protein constructs (N-FsII) were able to form soluble nanorings. These N-FsII-nanorings were efficiently recognized by either monoclonal antibodies specific for FsII, sera of F-immunized mice or palivizumab.…”
Section: Discussionmentioning
confidence: 94%
“…23 In calves, N-nanorings alone or co-administered with RSV P and M2-1 proteins, provide strong cellular immunity and significant but partial protection against virus replication and clinical symptoms upon bovine RSV challenge. 24,25 Importantly, we did not record signs of pulmonary disease exacerbation upon challenge of vaccinated mice or calves. 23,24 …”
Section: Introductionmentioning
confidence: 88%